The Rise of the Middle Class, Brazil (1839-1950) - María Gómez-León (European Historical Economics Society (EHES), 2015)
This article investigates the rise of the middle class in Brazil between the mid-nineteenth and mid-twentieth centuries and its connection with inequality. To this purpose Brazil's income distribution is explored from two dimensions: inequality and polarisation. A new middle class index (MCI), based on polarisation methods, is used to assess the evolution of the middle class in terms of both income and status. Results suggest that during the nineteenth century low income levels prevented the achievement of high inequality values and the emergence of a middle class. Then in the early twentieth century Brazil experienced a process of economic growth accompanied by increasing inequality in a Kuznetsian sense in which the middle class arose. Yet, despite rapid economic growth during the following decades, the continued increase of inequality, especially between 1930 and 1950, impeded the consolidation of the middle class and the reduction of poverty.
Keywords: D31; D63; N16; N36; O15; 330; Middle class; inequality; polarisation; Brazil